Teknik Effleurage Massage dan Kompres Hangat Berpengaruh terhadap Penurunan Tingkat Nyeri Afterpains pada Ibu Nifas di PMB A Kota Jakarta Selatan Tahun 2022 - Pipit Pitriani; Ageng Septa Rini; Rizkiana Putri (SIMFISIS Jurnal Kebidanan Indonesia, 2023)
Introduction: The puerperium (puerperium) is a period of recovery, starting from the completion of labor until the uterine organs return such as pre-pregnancy, this postpartum period is 6-8 weeks. Some of the physiological changes that occur during the puerperium are shrinkage of the uterus which is a process in which the uterus returns to its pre-pregnancy state. In the postpartum period, there is uterine involution accompanied by contractions of the uterus so that it can cause pain during contractions or term after pain. Objectives: The purpose of this study was to determine the effect of the Effleurage massage technique and warm compresses on afterpains pain in postpartum mothers in PMB A South Jakarta City 2022. Method: This research method used a quasi-experimental approach with a pre-posttest approach, a non-equivalent control group design of as many as 30 people. The research instrument used the Numeric Rating Scale (NRS) pain scale Observation sheet. Result: The results of the study using the Wilcoxon statistical test were obtained. P-value = 0.001 < = 0.05, with a negative rank p-value in the control group 15ª and 14ª in the intervention group meaning that there is an effect of warm compresses or effleurage massage techniques and warm compresses on after-pains pain in postpartum women. Conclusion: Effleurage massage and warm compresses showed a change before or after the intervention, but the warm compress group gave a greater effect than the group given effleurage massage and warm compresses.